Proceedings of the 15th International Heat Transfer Conference 2014
DOI: 10.1615/ihtc15.tbf.008857
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Heat Transfer Coefficients to Cylinders in Shallow Bubble Columns

Abstract: High heat transfer coefficients and large interfacial areas make bubble columns ideal for dehumidification. However, the effect of geometry on the heat transfer coefficients outside cooling coils in shallow bubble columns, such as those used in multi-stage bubble column dehumidifiers, is poorly understood. The generallyoverlooked entry and coalescing regions become important in shallow bubble columns, and there is disagreement on the effects of the coil and column diameters. In this paper, a method is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…We have found no correlation developed for tall columns that satisfacto-rily predicts the heat transfer coefficient in a shallow column, but we have demonstrated agreement with several correlations with respect to the dependence on superficial velocity [15]. One of these correlations is Deckwer's [18], which is straightforward and widely-used.…”
Section: Theoretical Backgroundmentioning
confidence: 77%
See 3 more Smart Citations
“…We have found no correlation developed for tall columns that satisfacto-rily predicts the heat transfer coefficient in a shallow column, but we have demonstrated agreement with several correlations with respect to the dependence on superficial velocity [15]. One of these correlations is Deckwer's [18], which is straightforward and widely-used.…”
Section: Theoretical Backgroundmentioning
confidence: 77%
“…We have previously shown that the heat transfer coefficient in a shallow column depends on the distance, H, from the sparger plate [15], and we wish to quantify this effect with a correlation that utilizes the vast amount of existing knowledge about heat transfer in tall bubble columns. Of the two correlations mentioned, Deckwer's is more straightforward.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Tow and Lienhard [11,12] also measured heat transfer rates up to more than 8,000 W/m 2 -K in shallow bubble columns, further justifying their use in the dehumidification side of an HDH system.…”
Section: Bubble Column Dehumidifiers In Hdhmentioning
confidence: 92%